ROLE OF PHYTOESTROGEN IN SUPPRESSING BONE TURNOVER IN A GROUP OF POSTMENOPAUSAL WOMEN - Rashid, Asma; Khurshid, Rukhshan; Latif, Aiza; Ahmad, Nazifa; Aftab, Latif (Journal of Ayub Medical College Abbottabad, 2010)
Background: Osteoporosis has emerged a major health hazard in postmenopausal women. The process of osteoporosis accelerates two year prior to menopause, reaching the peak level during first 3 years of menopause when women loss 3-5% of their bone mass per year. This study tried to find out the role of phytoestrogne in improving the bone mineral density and bone related biochemical parameters in group of postmenopausal women. Methods: Fifty postmenopausal women with age range 50-60 years were included in the study. Phytoestrogen with mineral supplement were given twice daily for 3 months. Biochemical parameters like serum calcium, magnesium, alkaline phosphatase, uric acid, total protein and oestrogen were determined before and after phytoestrogen therapy by autoanalyser and ELIZA (oestrogen assay). T-score before and after phytoestrogen were find out by densitometer DEXA. Results: The level of serum calcium, magnesium, uric acid and oestrogen was increased in women after taking phytoestrogen but significant difference (p<0.01) was only observed in case of serum calcium. Level of serum alkaline phosphatase and total serum protein were slightly increased with no significant different before and after phytoestrogen therapy. Value of T-score was although markedly decreased after phytoestrogen therapy but it showed no significant difference. Conclusion: It is concluded that as the early years of menopause are a period of rapid bone loss, and the risk for osteoporosis increases substantially, the habitual intake of soy protein and isoflavones may play a role in the retardation of bone loss. Keywords: Osteoporosis, Phytoestrogen, Postmenopausal status